2014
DOI: 10.1088/1674-1056/23/4/048107
|View full text |Cite
|
Sign up to set email alerts
|

Relation between martensitic transformation temperature range and lattice distortion ratio of NiMnGaCoCu Heusler alloys

Abstract: Relation between martensitic transformation temperature range and lattice distortion ratio of NiMnGaCoCu Heusler alloys *Wei Jun(韦 俊) a)b) , Xie Ren(谢 忍) a) , Chen Le-Yi(陈乐易) a) , Tang Yan-Mei(唐研梅) a) , Xu Lian-Qiang(许连强) a) , Tang Shao-Long(唐少龙) a) † , and Du You-Wei(都有为) a) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Wei et al already reported that the change in c/a ratio correlates with the thermal hysteresis of the martensitic transformation for a series of NiMnGaCoCu shape memory alloys with a tetragonal martensite [26]. That relation between c/a and thermal hysteresis could also explain the difference between the thermal hysteresis for the different series of alloys studied in this work: the Ni 50 Mn 25 Ga 25Àx Cu x series shows the highest values of c/a and thermal hysteresis, whereas the lowest values of c/a and the thermal hysteresis are shown by one of the Ni 50 Mn 25Àx Ga 25 Cu x alloys.…”
Section: Tem Observationsmentioning
confidence: 99%
“…Wei et al already reported that the change in c/a ratio correlates with the thermal hysteresis of the martensitic transformation for a series of NiMnGaCoCu shape memory alloys with a tetragonal martensite [26]. That relation between c/a and thermal hysteresis could also explain the difference between the thermal hysteresis for the different series of alloys studied in this work: the Ni 50 Mn 25 Ga 25Àx Cu x series shows the highest values of c/a and thermal hysteresis, whereas the lowest values of c/a and the thermal hysteresis are shown by one of the Ni 50 Mn 25Àx Ga 25 Cu x alloys.…”
Section: Tem Observationsmentioning
confidence: 99%
“…Ni-Mn-Ga based ferromagnetic shape memory alloys (FSMAs), which exhibit giant magnetic-field-induced strain (MFIS) in the martensitic phase, have attracted considerable attention due to their potential applications in new generation actuation and transduction devices. [1][2][3][4][5] A large MFIS of up to 10% has been reported in Ni-Mn-Ga. [6][7][8] The mechanism of giant MFIS is a reorientation of martensitic twin variants under an applied magnetic field by twin-boundary motion. So far, Ni-Mn-Ga FSMAs still have several characteristic shortcomings that greatly limit their potential applications.…”
Section: Introductionmentioning
confidence: 99%